2014
DOI: 10.1002/tesq.190
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety's Forgotten Study: The Case of the Anxious Preservice Teacher

Abstract: This article argues that nonnative preservice teachers are just as susceptible to foreign language anxiety as are inexperienced language learners, a claim carrying important implications for the EFL classroom. The results of the study described in this article indicate that anxious preservice teachers experience significant levels of language anxiety to a degree that may cause them to avoid using the target language and language‐intensive teaching practices in their classrooms. The article also proposes steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 66 publications
3
33
0
Order By: Relevance
“…Although Kunt (1997) found low levels of anxiety in students learning English using the FLCAS, Kunt and Tüm (2010) and Tüm (2014) found high levels of anxiety with non-native English-speaking student teachers by examining their responses to the open-ended sections of the FLCAS. In addition, using the FLCAS, Gülmez (2012) researched Turkish students learning French.…”
Section: Anxiety and Multilingualism In The Turkish Contextmentioning
confidence: 95%
“…Although Kunt (1997) found low levels of anxiety in students learning English using the FLCAS, Kunt and Tüm (2010) and Tüm (2014) found high levels of anxiety with non-native English-speaking student teachers by examining their responses to the open-ended sections of the FLCAS. In addition, using the FLCAS, Gülmez (2012) researched Turkish students learning French.…”
Section: Anxiety and Multilingualism In The Turkish Contextmentioning
confidence: 95%
“…However, the results also revealed that maladaptive perfectionists were found to be more anxious than adaptive and nonperfectionist. In a Turkish context study (Tum, 2015), the result indicated that anxious pre-service teachers experience significant levels of language anxiety to a degree that might cause them to avoid using the target language and language-intensive teaching practices in their classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…She argued that teachers' discomfort is likely to lead to students also believing they cannot use the language effectively. Teacher language anxiety also affects self-confidence and instructional choices, as shown in more recent research that provides support for Horwitz's contention (Machida, 2016;Tum, 2015;Yoon, 2012). Confidence, it seems, is bound up with a sense of professional self-efficacy, and increases in confidence can lead to more effective teacher agency in the classroom, a stronger sense of identity as a language teacher, and greater autonomy in making instructional decisions (Senior, 2012).…”
Section: Developing Classroom English Competencementioning
confidence: 92%